Short Answer
The expression (y¬π)‚ŵ – 1 simplifies to y‚ŵ after applying exponent rules. The final result is 10y, aligning with option D.
Step 1: Understanding the Expression
Begin with the expression you need to simplify: (y¬π)‚ŵ – 1. This expression utilizes the rules of exponents, and it is imperative to know what these rules are in order to manipulate the equation effectively. Recognizing how different exponent rules apply will be essential in simplifying this expression into a more manageable form.
Step 2: Applying Exponent Rules
Utilizing the rules of exponents, you can start simplifying the expression. The relevant rules include:
- an * 1 = n * a
- (a * b)c = ab * c
- a-b = ab * 1
By applying these rules to the expression, we can continue simplifying to obtain a more concise version of what we started with.
Step 3: Arriving at the Final Result
After applying the exponent rules, the expression (y¬π)‚ŵ – 1 simplifies to y10. This follows the calculations:
- (y)⁵ * 1 = y²
- (y²) * (5¹) = y10
Thus, the expression simplifies to 10y, matching choice D.